2022
DOI: 10.1212/wnl.0000000000200384
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Cognitive Changes in Genetic Frontotemporal Dementia Within the GENFI Cohort

Abstract: Background and ObjectivesDisease-modifying therapeutic trials for genetic frontotemporal dementia (FTD) are underway, but sensitive cognitive outcome measures are lacking. The aim of this study was to identify such cognitive tests in early stage FTD by investigating cognitive decline in a large cohort of genetic FTD pathogenic variant carriers and by investigating whether gene-specific differences are moderated by disease stage (asymptomatic, prodromal, and symptomatic).MethodsC9orf72, GRN, and MAPT pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Although worse performance on some cognitive domains can be evident at the pre-symptomatic stage of FTD, in comparison with non-carrier controls [19, 21, 61], it is difficult to distinguish genetic mutation carriers from non-carriers simply based on performance on cognitive tasks. We found no significant difference in cognitive performance between genetic mutation carriers and non-carriers at the pre-symptomatic stage, confirming that genetic mutation carriers maintain similar overall cognition as non-carriers before symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…Although worse performance on some cognitive domains can be evident at the pre-symptomatic stage of FTD, in comparison with non-carrier controls [19, 21, 61], it is difficult to distinguish genetic mutation carriers from non-carriers simply based on performance on cognitive tasks. We found no significant difference in cognitive performance between genetic mutation carriers and non-carriers at the pre-symptomatic stage, confirming that genetic mutation carriers maintain similar overall cognition as non-carriers before symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits are measurable using neuropsychological tasks in the prodromal stage and recent work has shown that the domains involved are relatively specific to the different genetic groups, e.g. early deficits of episodic memory and language are seen in prodromal MAPT mutation carriers [33,34], although executive function and social cognition deficits are commonly seen across the genetic groups [35]. Recently, a cognitive composite (the GENFI-Cog) unique to each genetic group has been developed for use in the prodromal period decreasing the sample size required for trials [36 ▪▪ ].…”
Section: Prodromal Stagementioning
confidence: 99%
“…The Genetic Frontotemporal Dementia Initiative (GENFI) is such an international enterprise. GENFI studies have demonstrated structural imaging and cognitive changes 5–10 years before the expected onset of symptoms (Rohrer et al, 2015), sensitivity of cognitive measures in tracking progression (Poos et al, 2022) and gene‐specific differences in cognitive profile (Poos et al, 2022). Research criteria for prodromal bvFTD have been proposed (Barker et al, 2022).…”
Section: Recent Developments: Pre‐clinical Ftdmentioning
confidence: 99%